PENGARUH FAKTOR-FAKTOR KEPUTUSAN KONSUMEN TERHADAP PEMILIHAN JASA CLEANING SERVICE ONLINE - Mutiarawan - - (Jurnal Akademika, 2021)
This study aims to determine whether there is a simultaneous and partial influence of cultural, social, personal and psychological variables on consumer decisions in choosing CV cleaning services. Indoclears Malang. This research is a descriptive study with a quantitative approach. In this study, the number of samples used followed the total population of 40 respondents. The research method used is multiple linear regression analysis (multiple linear regression method), Cultural factors have a partially significant effect on consumer decisions. Social factors have a partially significant effect on consumer decisions. Personal factors have no partially significant effect on consumer decisions. Psychological factors have a partially significant effect on consumer decisions. Cultural, social, personal and psychological factors simultaneously have a significant effect on consumer decisions. Keywords: culture, social, personal and psychology, consumer decisions